Collaborative Governance in Waste Management in Kupang City - Banunaek, Yulia Puspikasari; Djani, William; Nursalam, Nursalam (International Journal of Economics Development Research (IJEDR), 2024)
The waste problem in Indonesia, including Kupang City, is a pressing issue due to increasing waste production from various sources, such as households, offices, markets, and public facilities. Collaborative Governance involving stakeholders (government, private sector, and community) is essential for addressing this issue. This study aims to analyze Collaborative Governance in Kupang City's waste management, focusing on trust among participants, distributive accountability, and information sharing. Findings reveal that: (1) Trust among participants is minimal, with limited community trust in government programs; (2) Distributive accountability is practiced through shared governance and decision-making; and (3) Information sharing is conducted through government-led socialization efforts, such as waste bank awareness programs. Recommendations include enhancing government-community trust, conducting regular surveys on waste bank participation, and improving public counseling and facilities to promote effective waste management.